P-434 Is there an association between pre-ovulatory estradiol levels and placental pathology of singleton livebirths conceived with gonadotropins/intrauterine insemination (Gn/IUI) treatments?. (30th June 2022) - Fitz, V; Cherouveim, P; Hammer, K; Jiang, V; Sacha, C; Dimitriadis, I; Bormann, C; James, K; Roberts, D; Souter, I
Abstract: Study question: Is pre-ovulatory estradiol level associated with placental weight (PW) and abnormality rates (PAR) in singleton livebirths resulting from gonadotropins/intrauterine insemination (Gn/IUI) treatments? Summary answer: In Gn/IUI-conceived, singleton-livebirths with available placental pathology, an association was noted between preovulatory estradiol levels and PW, but not between estradiol and PAR. What is known already: Data suggest an association between ART and placental-mediated pregnancy complications, as well as increased rates of placental pathology. Supraphysiologic levels of preovulatory estradiol have been implicated in abnormal placentation. Whether such an effect is noted in Gn/IUI treatments, where levels of estradiol are lower, nevertheless supraphysiologic, remains unknown. Study design, size, duration: We retrospectively reviewed data from 560 Gn/IUI-conceived, singleton-livebirths (1/2004-1/2021) recruited from a large academic fertility center. Placental pathology information was available from 218 cycles. These cycles were stratified by pre-ovulatory estradiol levels in quartiles [Q1(lower)-Q4 (higher)]. PW [grams & percentiles (%iles)], and rates of placental abnormalities (classified as anatomic, inflammatory, infectious, and vascular/thrombotic ) were compared between groups. Participants/materials, setting, methods: Participants: Women with Gn/IUI-conceived, singleton-livebirths with available placental pathology. Outcome Measures: PW and PAR. Statistics: Regression analysis was utilized to estimate the association of pre-ovulatory estradiol %iles with PW and PAR, adjusting for potential confounders (PW: maternal and gestational age, BMI, infertility diagnosis, medical complications, infant gender; PAR: maternal and gestational age, BMI, race). Adjusted Odds Ratios (OR) with 95%CI were calculated for the latter. Main results and the role of chance: Mean PW(±SD) in grams were 477.3(±124.1), 445.9(±107.4), 451.2(±113.9), and 438.9(±107.0) in Q1 through Q4 (p=.368). Small placentas (≤10 th PW %ile) accounted for more than a third of the total in all estradiol quartiles (37.5%, 49.2%, 37.5%, and 42.2%, p=.539, Q1-Q4, respectively). Similarly, increasingly higher percentages of placentas ≤25 th PW %ile were noted with increasing estradiol quartiles (47.9%, 57.6%, 62.5% and 64.5%, in Q1-Q4 respectively, p=.347). After adjusting for potential confounders, we noted a mean 13.7 grams decrease in PW between each subsequent estradiol quartile [ adjβ-coeff (95%CI): -13.7(-27.7-0.3), p=.055]. When estradiol levels were analyzed as a continuous variable, an inverse association with PW [ adjβ-coeff (95%CI): -0.08 (-0.16-(-0.01)), p=.026] was noted. Adjusted ORs for small placenta did not differ between estradiol quartiles or when estradiol was analyzed as a continuous variable [adjORs(95%CI): 1.73(0.74-4.07), 1.10(0.47-2.55), 1.81(0.69-4.72), for Q2-Q4, Q1 as ref. ; 1.001(1.000-1.003), p=.167; respectively]. There was no significant association between placental abnormality rates (PAR) and estradiol, either before or after adjustment [adjORs(95%CI): i) Anatomic : 1.16(0.49-2.74), 1.52(0.65-3.59), and 1.17(0.45-3.02); ii) Inflammatory : 0.40(0.13-1.25), 0.79(0.28-2.17), and 1.25(0.42-3.73); iii) Infectious : 0.89(0.35-2.25), 1.67(0.68-4.13), and 0.58(0.20-1.67); iv) Vascular/thrombotic : 0.88(0.37-2.08), 1.87(0.80-4.41), and 0.95(0.36-2.49); for Q2-Q4 vs. Q1]. Limitations, reasons for caution: There are several limitations, including the retrospective design, possible selection bias resulting from the decision to obtain placental pathology. Nonetheless, birth weights did not differ between those with and without placental pathology. Estradiol levels, albeit supraphysiologic, are much lower than those in ART and differences might be masked. Wider implications of the findings: In Gn/IUI-conceived, singleton-livebirths with available placental pathology, an association was noted between preovulatory estradiol levels and placental weight, but not between estradiol and the rate of specific placental abnormalities (PAR). Since estradiol levels are lower than those observed in ART, an association might have been missed. Trial registration number: not applicable